A novel rejuvenation program for cancer patients at Kaivalyadhama, India - Lee Majewski; Ananda Balayogi Bhavanani (Wolters Kluwer Medknow Publications, 2014)
Background: The modern intensive treatment for cancer leaves the patients physically and mentally exhausted by the end of it. There is great potential for Yoga, the original mind-body medicine, in such a situation as it conjointly emphasizes body, mind, and spirit, which may be particularly useful for enhancing patients' social and spiritual well-being. Some studies have reported the effectiveness of Yoga, meditation, and mindfulness as a rehabilitative and palliative therapy in various types of cancer. Objectives: With the above background in mind, we created a 3-week residential program for cancer patients to empower them in their journey, "back to health." The curriculum was geared specifically for those who had undergone chemotherapy and/or radiation. Methods: The program utilized the sister life sciences of Yoga and Ayurveda with a healthy dose of self-education to assist patients in their recovery from the devastation of cancer and its modern treatment. The modes of reintegration used in this program were designed to specifically address the physical, mental, and psychic (spiritual) needs of the participants. The curriculum included various asanas, kriyas, pranayama, mudras, and bandha, as well as chanting. Ayurvedic treatment based on panchkarma science was designed and applied according to each patient's disposition. An educational component was included to inform patients of potential carcinogenic factors in their life and to change their mindset and attitudes from victimhood to self-empowerment. In order to scientifically validate the program, physiological, biochemical, psychological, and Ayurvedic assessment of tridoshas was carried out. Conclusion: Our special Cancer Rehabilitation Yoga program is expected to have several beneficial effects for those recovering from the aftermath of anti-cancer therapies even at 3-month follow-up. Subjective observations so far reveal that the program led to overall empowerment of the participants.